Spatial Planning in Service Delivery Towards Distributive Justice in South Africa - Magidimisha, Hangwelani Hope; Chipungu, Lovemore (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This volume presents a detailed synthesis of the historical, present-day and future state of service delivery in South Africa. The generation and distribution of services in any geographical space has been and is always a source of inequality in human society. Thus, in the context of spatial planning, space is the major factor through which distributive justice and sustainable development can be achieved. To examine the continuation of spatial inequality in service delivery, the authors employed both qualitative and quantitative research methods in a multi-pronged approach, utilizing empirical data from the Vembe District in Limpopo, data from the South African Index of Multiple Deprivation, and representative attitudinal data from the South African Social Attitudes Survey. Ultimately, this study examines spatial differences in living environments with a focus on the distribution of household services and discusses strategies to achieve spatial equality.